Peningkatan Kapasitas Panwaslih dalam Penegakan Hukum Pelanggaran Pemilu di Kabupaten Aceh Barat Daya - Asmaul Husna; Jefrie Maulana; Eza Aulia; Dara Quthni Effida; Yuhdi Fahrimal (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
The practice of violating electoral rules is a phenomenon that often occurs in the election process, especially during the campaign period. All violations that occur must be responded to by taking action through law enforcement in accordance with applicable laws and regulations in order to maintain the implementation of democratic elections and strengthen popular sovereignty. One of the institutions that has the authority in terms of law enforcement against election violations is the Election Supervisory Committee (Panwaslih). However, the low capacity, knowledge, and understanding of field supervisory officers make it difficult to take action against election violations during the campaign period. This community service activity aims to increase the capacity of field supervisory officers in Southwest Aceh Regency so that they have knowledge and understanding related to election supervision so that they can work optimally. The service activities were carried out through lectures and focus group discussions with a statute approach and case study approach. Participants in this activity were all field supervisory officers in Southwest Aceh Regency. The results obtained from this service are (1) participants understand and can identify potential election violations during the campaign period and (2) participants understand the legal basis and identify articles that can be imposed for each election violation during the campaign period. This activity will be a provision for election supervisors in Southwest Aceh Regency and they will apply this understanding in carrying out their duties and functions as supervisors of the implementation of elections in realizing a democratic party that is based on direct, general, free, confidential, honest and fair.